Modular porous polymer-based microcapsules for trapping and near-infrared light-triggered killing of bacteria via gold nanorods - Conzelmann, Nina; Benimeli Borràs, Ariadna; Muduli, Saradaprasan; Schramm, Anastassiya; Jeschenko, Pascal Max; Platzman, Ilia; Spatz, Joachim P. (ACS applied nano materials, 2024)
Due to the increasing occurrence of antibiotic-resistant bacterial strains worldwide, there is an urgent need for developing antibiotic-independent strategies to combat bacterial infections. In this study, we developed a modular approach for trapping, retaining, and killing bacteria by means of porous, poly(lactic-co-glycolic acid) (PLGA)-based microcapsules with integrated gold nanorods (AuNRs). AuNRs were coated with thiol-functionalized PLGA beforehand to ensure efficient integration into the hydrophobic microcapsule shells. For the efficient generation of AuNR-functionalized microcapsules, we designed and developed a fast and reliable one-pot bulk emulsification production method. When exposing the AuNR-decorated microcapsules to near-infrared light, both motile and nonmotile bacteria were killed in a highly localized manner due to AuNR-generated heat. Importantly, fibroblast cell viability tests performed with AuNR-decorated microcapsules revealed good biocompatibility of the system. Such a modular antibacterial system can be employed in various applications, including, but not limited to, implant coatings, flushing solutions, and sewage treatment.
Gesehen am 27.03.2025